Tempurung Kelapa Sawit (TKS) sebagai Bahan Baku Alternatif untuk Produksi Arang Terpadu dengan Pyrolegneous / Asap Cair Oil-Palm Shell as the Alternative Raw Material for the Integrated Production of Charcoal with Pyroligneous Acid / Liquid Smoke - Tjutju Nurhayati; Desviana Desviana; Kurnia Sofyan (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
Oil-palm shell (Ops) can be regarded as a fuel, because it has calorific value almost similar to that of wood.  Ops is generated as waste from crude palm oil industries, and its utilization as raw material are based on its chemical composition, which contains among others cellulose, hemicellulose, and lignin, as the wood does so.Pyroligneous acid or smoke liquid is produced through the condensation of gas/smoke fraction as generated during the charcoal manufacture from wood or other ligno-cellulosic stuffs such as Ops.  Such liquid is also famously called wood vinegar that seems worth for further development. The production of pyroligneous acid/wood vinegar can therefore be integrated with that of charcoal.As the relevance, experiment on integrated production of charcoal and pyroligneous acid/wood vinegar was conducted in the Sakuraba-type portable kiln.  The raw material was Ops and Mangium (Acacia mangium Willd) wood, the latter used as the comparison/control.  The results revealed that the yield of Ops charcoal was lower than that of Mangium charcoal, i.e. 11.37% vs. 24%, respectively. However, the yield of Ops pyroligneous acid (24.8%) was almost comparable to that of Mangium pyroligneous acid (24.5%).  In addition, the qualities of charcoal from both Ops and Mangium wood could meet those of Indonesian National Standard (SNI). Likewise, the qualities of their corresponding pyroligneous acids/wood vinegars from both could also comply with those of Japan wood vinegar